KRIYA TEKSTIL TIE-DYE (IKAT CELUP): SEBUAH MEDIA EKSPLORASI ESTETIS YANG POPULER - Suryo Tri Widodo (Institut Seni Indonesia Yogyakarta, 2012)
Tie-dye becomes the one of the most popular craft textile, which is known almost all over theworld including in Indonesia. Making motif on to the fabric using tie-dye techniques is very easy to belearned, beside there are many kind of simple technics on it. These techniques are very unique andcould be developed and explored without limited. The unpredictable effects of motifs sometimes mayappear and can be resulted from tie-dye techniques.In this article we will study about tie-dye in many aspect i.e. term of tie-dye, tradition andculture background of tie-dye, mainly showing about tie-dye techniques, and a few tie-dye products.This paper expected give the wide describing and inspiring about tie-dye in craft textile works or tiedyeas an expression of fine art.Keywords: tie-dye, resist-dye, textile motif, craft textile, aesthetic exploration